Parabacteroides acidifaciens sp. nov., isolated from human faeces. Issue 3 (17th January 2019) - Wang, Yu-Jing; Xu, Xin-Jie; Zhou, Nan; Sun, Yutong; Liu, Chang; Liu, Shuang-Jiang; You, Xin
Abstract : A polyphasic taxonomic approach was applied to characterize an anaerobic bacterial strain, 426-9 T, that was isolated from human faeces. The strain was Gram-stain-negative, non-motile, non-spore-forming, non-pigmented and rod-shaped. Strain 426-9 T grew anaerobically at 20–45 °C (optimally at 37–40 °C) and at pH 6.0–10.0 (optimally at pH 6.0–8.0). The major polar lipids were phosphatidylethanolamine, seven amino phospholipids and three phospholipids. The major fatty acids of strain 426-9 T were anteiso-C15 : 0 and iso-C17 : 0 3-OH, and the predominant respiratory quinones were menaquinones MK-9 and MK-10. End-products of glucose fermentation were acetate, propionate, iso-butyrate and iso-pentanoate. 16S rRNA gene sequence analysis showed that strain 426-9 T was a member of the genus Parabacteroides . The level of 16S rRNA gene sequence similarity of strain 426-9 T to the type species of the genus, Parabacteroides distasonis ATCC 8503 T, was 91.0 %. Within the genus Parabacteroides, strain 426-9 T was phylogenetically closely related to Parabacteroides johnsonii M-165 T (96.0 % 16S rRNA gene sequence similarity). The draft genome of strain 426-9 T comprised 5.15 Mb with a DNA G+C content of 45.9 mol%. A total of 4088 genes were predicted and, of those, 3744 were annotated. On the basis of phenotypic, chemotaxonomic and phylogenetic characterization, strain 426-9 T represents a novel species within the genus Parabacteroides, for which the name Parabacteroides acidifaciens sp. nov. is proposed. The type strain is 426-9 T (=CGMCC 1.13558 T =NBRC 113433 T ).